Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae) - Wallace, Robert Lee; Kordbacheh, Azar; Walsh, Elizabeth J. (Zootaxa, 2018)
Although the most widely used key to the Rotifera subsumes six species of the sessile genus Limnias within two species groups (L. ceratophylli and L. melicerta), the original descriptions of these forms are sufficiently different to recognize them as distinct entities. We used these descriptions and all available literature on these species to develop dichotomous and formula keys to the six species based on easily recognizable morphological characters. As part of our review we added relevant ecological information from published sources, as well as our own data. We also discuss the need for additional observations of morphological, behavioral, life history, and genetic features to better understand the diversity of this widespread genus.